Physionomies d’une cité grecque. Développements stylistiques de la coroplathie votive archaïque de Tarente - Michael Anthony Fowler (Les Carnets de l’ACoSt)
The present monograph is a revised and expanded version of Ágnes Bencze’s dissertation, defended at the University of Paris I in December 2005. The study, the result of over a decade of research, including autopsy of relevant materials held in several museum storerooms throughout Europe, offers the first systematic stylistic classification of all extant types of mold-made votive terracottas produced in archaic Tarentum. Through the adoption of a broad chronological frame and an exhaustive approach to the corpus of evidence, the author aims to trace the stylistic development of local coroplastic production from its origins in the latter half of the seventh century to the emergence of the distinctly Tarentine form of reclining banqueter in the final decades of the sixth-century. In so doing, the author treats the diverse stylistic influences to which local artisans seem to have been exposed, whether directly or indirectly, and the (art) historical implications of their reception.